Calcareous Nannofossil Biostratigraphy of Tonasa Formation at Barru River Traverse, South Sulawesi, Indonesia - Meutia Farida; Asri Jaya; Jimmi Nugraha (Geological Agency, 2022)
DOI:10.17014/ijog.9.3.371-381Barru is one of the areas in South Sulawesi where the stratigraphic sequences of lithology from Mesozoic to recent are well exposed. The Tonasa Formation is quite widespread in this area, and it is interesting to find out its various aspects related to the carbonate rock development. For this reason, the distribution of nannofossils were recorded and the relative age of Tonasa Formation was determined using nannofossil collected by measuring section at Barru River. The calcareous nannofossil assemblages are moderate to poor preserved. A total of twenty-three species were identified from the bottom to the top of the interbedded marl and limestone. The nannofossil assemblage-based biostratigraphy of the studied area was shown by the First Occurrence (FO) and Last Occurrence (LO) of the marker species. As for the results, there were six data found in this study, i.e. FO and LO of Reticulofenestra umbilicus, FO of Sphenolithus pseudoradians, LO of Discoaster saipanensis, LO of Calcidiscus formosus, and LO Reticulofenestra bisectus. Based on the noted nannofossil data, the determined age of Tonasa Formation at Karama area included NP 15 – NN 1 or CP 13 - CN 1a, and equivalent to Middle Eocene until Early Miocene. The result shows important data that will contribute significantly in age constraint of Tonasa Formation